Incomplete systemic movement of Xanthomonas campestris pv. musacearum and the occurrence of latent infections in xanthomonas wilt-infected banana mats - Ocimati, W.; Nakato, G.V.; Fiaboe, K.K.M.; Beed, Fenton D.; Blomme, Guy (Wiley, 2015)
Management of banana xanthomonas wilt (XW) (caused by Xanthomonas campestris pv. musacearum, Xcm) has been impeded by poor adoption of control options that are complex, cumbersome and costly. To improve XW management, this study investigated Xcm survival and latent infections in subsequent generations, survival of latently infected planting materials (suckers), incidence of latent infections in symptomless plants in mats having diseased plants, and XW status across farms and markets in districts previously devastated but currently endemic. On‐station experiments were protected from new infections. Latent bacteria at low levels were detected in up to 20% of the third generation suckers, with a significant (P < 0·05) reduction (43–20%) in subsequent generations. Only 3–6% of latently infected suckers succumbed to XW. Incidence of Xcm in symptomless suckers from farmers' fields (with up to 70% incidence) was low (3%) while it increased (8–25%) with disease severity in mats in controlled experiments. In the surveyed districts, incidence had significantly declined with yields observed to have recovered relative to earlier reports, although latent infections remained high. This study provides evidence that if new infections are prevented, fields with high XW incidence can be rejuvenated. It showed incomplete systemic movement of Xcm in mats coupled to a gradual decline of bacterial load in subsequent generations to levels that cannot initiate disease. These studies explain the current successes in farms practising single diseased plant removal instead of whole mat rouging, and gives hope to farmers lacking access to clean planting material.